Mapping Seismic Vulnerability Index (Kg) For Earthquake Swarm Activity In Western Halmahera, Indonesia - Rohima Wahyu Ningrum; Hendra Fauzi; Wiwit Suryanto; Estuning Tyas Wulan Mei (Faculty of Engineering, Malikussaleh University, 2018)
This research was conducted to determine seismic vulnerability index based on microtremor analysis and make microzonation of seismic vulnerability index in West Halmahera district. The microzonation is expected to be used for regional development based on earthquake disaster mitigation. The swarm earthquake that occurred in West Halmahera regency, although not significant in terms of loss of life, greatly affected the stability and capacity of the region in terms of infrastructure development. Data acquisition at the research location obtained 56 point locations. Microtremor data were analyzed using the Horizontal to Vertical Spectral Ratio (HVSR) method to obtain frequency and amplification values that can be used to calculate the value of seismic vulnerability (Kg) from a region. The results obtained are the seismic vulnerability index (Kg) value in West Halmahera Regency is 0 cm/s2 - 31341.52 cm/s2. The highest Kg value is located in Jailolo sub-district at point D10 which is 10397.1 cm/s2. This is closely related to the total amount of damage to buildings in Jailolo Subdistrict due to the earthquake in November 2015 to February 2016. Whereas for other Subdistricts classified as medium to low Kg values, it can be concluded that having a stable soil structure.